2009
DOI: 10.1111/j.1751-553x.2007.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated platelets and thrombopoietin in schistosomiasis patients

Abstract: Schistosomiasis mansoni is a non-cirrhotic liver disease. In cirrhosis patients with portal hypertension, a decreased number of reticulated platelets associated with increased thrombopoietin serum levels were reported. We previously reported a 120/nl platelet cutoff level as a marker of clinically significant portal hypertension in schistosomiasis patients. To evaluate reticulated platelet counts and thrombopoietin serum levels (TPO) in schistosomiasis patients and correlate them with portal hypertension marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Levels of protein C and antithrombin were significantly lower in our patients compared to the healthy controls, presumably reflecting hepatic dysfunction caused by portal hypertension and advanced periportal fibrosis [10], [20]–[22]. Although bleeding events in hepatosplenic schistosomiasis are associated with portal hypertension [20], the deficient production of coagulation factors does not seem to aggravate the situation due to a balance between the reductions in pro- and anti-coagulation proteins.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Levels of protein C and antithrombin were significantly lower in our patients compared to the healthy controls, presumably reflecting hepatic dysfunction caused by portal hypertension and advanced periportal fibrosis [10], [20]–[22]. Although bleeding events in hepatosplenic schistosomiasis are associated with portal hypertension [20], the deficient production of coagulation factors does not seem to aggravate the situation due to a balance between the reductions in pro- and anti-coagulation proteins.…”
Section: Discussionmentioning
confidence: 84%
“…Köpke-Aguiar et al [20] also reported that levels of thrombopoetin and reticulated platelets are normal in schistosomiasis patients with portal hypertension and that the bone marrow produces normal amounts of platelets. Thrombocytopenia in schistosomiasis patients may occur because of splenic retention due to poor portal blood drainage, or because platelets are trapped in the sinusoidal spaces of the fibrotic liver [20]. Our study confirms that thrombocytopenia is common in patients with hepatosplenic schistosomiasis, and that this tends to be higher in the advanced stages of periportal fibrosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The strong correlation between the number of platelets and the spleen diameter observed in SM could also be strengthened by the absence of other factors that induces thrombocytopenia, which are found in the cirrhosis (25) . For example, in this parasitic disease the production of thrombopoietin is higher that described in the cirrhotic patients, as well as in the SM antibodies antiplatelets are not observed as found in the HCV chronic liver disease (11,25) . Recently, a smaller number of platelets and larger spleen diameter have been described in patients with SM and with esophageal varices in comparison to those without varices (1) .…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, Koepke-Aguiar et al (11) found more severe thrombocytopenia in patients with advanced forms of hepatosplenic schistosomiasis with portal hypertension. In addition, studying 47 patients with SM and 13 controls, Lambertucci et al (12) found a mean number of 194 x 10 9 /L platelets in the controls and 44 x 10 9 /L in patients with severe periportal fibrosis, as assessed by ultrasound.…”
Section: Discussionmentioning
confidence: 99%